Fabrication of catalyst layer for proton exchange membrane water electrolyzer: I. Effects of dispersion on particle size distribution and rheological behavior - Liu, Chen; Luo, Maji; Zeis, Roswitha; Chuang, Pa Ya Abel; Zhang, Ruiming; Du, Shaojie; Sui, Pang Chieh (International Journal of Hydrogen Energy, 2024)
The catalyst layers of proton exchange membrane water electrolyzer are generally made by coating ink mixtures of catalyst and ionomer to the membrane. The particle size and stability of such inks are crucial to the formation of the catalyst layer's microstructure and overall cost. In this paper, the characteristics and stability of iridium oxide inks are investigated. The effects of inks dispersed by sonication and ball-milling on the particle size distribution, zeta potential, and viscosity of the catalyst inks are investigated. For both dispersion methods, it is found that increasing the dispersion time and strength effectively reduces the average particle size as expected. The inks prepared by ball-milling tend to have narrower and smaller size distribution than those by sonication. The rheological behavior of these inks is found to be slightly non-Newtonian. Ball-milling appears to increase the ink viscosity. A dual-dispersion technique that combines both dispersion steps is developed in the present study. The inks made with this procedure yield smaller size distributions than those with single dispersion, thus a higher specific catalyst area that can reduce catalyst loading and cost. These inks are also found to have a long shelf life remaining homogeneous.
Created from Fastlane, Scopus look-up
Keywords: Ball-milling; Catalyst ink; Particle size distribution; PEM Water electrolyzer; Rheology; Sonication